RIF1 promotes replication fork protection and efficient restart to maintain genome stability - Chirantani Mukherjee (Nature Portfolio, 2019)
Replication fork degradation can result in genome instability. Here authors reveal a role for Rif1 protein in protecting stalled replication forks from undergoing extensive, DNA2-dependent, degradation.